(untitled) (ModaPalavra e-periódico, 2019)
The article deals with color variations in the traditional costumes of the baianas over the past decades, through interpretations of the entertainment industry (Carnival), of artistic productions based on upcycling and tourism. It aims to draw an aesthetic and symbolic parallel between its matrix composition, which includes a set of clothing pieces, turban, accessories and footwear (LODY, 1996, 2003), and the succeeding derivations along with its original social and religious content, including new morphologies and colors presented through the TV media, in exhibitions and in the everyday life of the streets of Salvador. Assuming that thetraditional costume has an African-Brazilian identity, deriving from a socio-religious situation in which the color is a key element (LODY, 1996, 2003), we intend to seek in its ontology essential references to the interpretation of their new morphologiesand meanings, assigned by the colors, incorporating materials and subtraction of elements of its originalcomposition.